Study of the effect of filling combination on impact energy absorption of parts manufactured in pla using cast filament manufacturing - Drozda, Fabiano Oscar; Silva, Ricardo Junior de Oliveira; Chixaro, Davi Salvini; Bravo, Dayane Perez (Brazilian Journal of Production Engineering, 2024)
Filament Fusion Manufacturing (FFF) is one of the most widespread additive manufcturing technologies. However, printed parts often have lower reliability compared to those produced by traditional manufacturing processes. Therefore, investigating the mechanical behavior of these parts is an important research topic and common interest among academics and manufacturers. This study proposes a new approach to design the internal structure of parts, combining two distinct regions with different fillings. The objective was to investigate the behavior of this new mesostructure on the toughness of the parts. For this, two sets of PLA test specimens were manufactured. The first built with single fill and the second with hybrid fill. The specimens were tested by Charpy Impact according to ASTM D6110-10. The results analyzed by ANOVA and the microstructure by optical micrographs. The use of the hybrid resource proved to be efficient in increasing toughness for fill densities of 20%. For samples with fill density above 50%, the increase in toughness was not significant, as printing time and material consumption for manufacturing increased. In situations where lighter structures with greater resistance to impact are desired, the use of hybrid filling has significant relevance.
Keywords: Fused Filament Fabrication; Mesostructure; hybrid infill; Charpy test